Sustainable Growth Rate of Textile and Apparel Segment of the Indian Retail Sector (Global Journal of Management and Business Research, 2011)
The textile and apparel segment dominating the retail sector of India with a contribution output of 39% draws attention to bid whether the growth rate being enjoyed by this sector currently is sustainable or not. Sustainable growth rate model can provide an excellent structure to describe the growth path of retail businesses. The current paper first describes in detail the textile and apparel segment of the Indian retail sector followed with the meaning and utility of sustainable growth rate (SGR). The third section of the paper reviews the growth rate in retail sector at global and Indian level. The last section analyses SGR of selected companies of apparel segment of retail sector in India for the duration of last five years from 2006 to 2010 followed with the discussion of analysis and conclusion indicating that for the firms to maintain an orderly growth, they have to work on keeping a consistent level in profit margins, asset turnover, leverage, and retained earnings. Only then they can manage to grow their sales at the rate of SGR.
Keywords: Textile and apparel retail sector; retention rate; profit margin; financial leverage; sustainable growth rate